ST8SIA6-AS1, a novel lncRNA star in liver cancer - Qiu, Cheng; Fan, Haoran; Tao, Siyu; Deng, Ziqing (Frontiers in Cell and Developmental Biology, 2024)
Liver cancer is one of the most lethal gastrointestinal malignancies. Emerging evidence has underscored the pivotal role of long non-coding RNAs (lncRNAs) in tumorigenesis, with ST8SIA6-AS1 identified as a novel oncogenic lncRNA contributing to liver cancer progression. ST8SIA6-AS1 is consistently upregulated in hepatic cancer tissues and is strongly associated with unfavorable prognosis. Moreover, it demonstrates high diagnostic efficacy in detecting HCC. ST8SIA6-AS1 is involved in various cellular processes including proliferation, migration, and invasion, primarily through its function as a competing endogenous RNA (ceRNA), thereby facilitating hepatocarcinogenesis and disease advancement. This review provides a detailed examination of the molecular functions and regulatory mechanisms of ST8SIA6-AS1 in hepatocellular carcinoma (HCC) and highlights its potential as a promising biomarker for liver cancer, aiming to propel the development of innovative therapeutic strategies for HCC management.